Eruption! : volcanoes and the science of saving lives - Rusch, Elizabeth (Scientists in the field., 2013)
An account of the work of volcanologists Andy Lockhart, John Pallister, and their team describes their life-risking efforts to investigate dangerous volcanoes that pose threats to more than one billion people worldwide.